Logico-semantic relations and their realization in chapter 5 White fang and the Indians" in the novel " White fang" by Jack London - Nguyễn, Thị Phượng (University of Languages and International Studies, 2017)
This paper investigates logico-semantic relations between clauses in clause complexes. The study first re-examined some basic concepts of systemic functional grammar and two types of logico-semantic relation – expansion and projection. Then, Chapter 5 “Whi (...)